2000
DOI: 10.1002/etc.5620190213
|View full text |Cite
|
Sign up to set email alerts
|

Burrowing owls and agricultural pesticides: Evaluation of residues and risks for three populations in California, USA

Abstract: We examined selenium, organophosphorus, and organochlorine pesticide residues in egg, footwash, and feather samples from burrowing owls in three populations in central and southern California. Eggs from all sites contained detectable levels of p,p′‐dichlorodiphenyldichloroethylene, with the San Joaquin Valley site containing up to 33 μg/g (geometric mean x¯ = 7.52). Only low levels of polychlorinated biphenyls were detected, however (geometric mean x¯ = 1.98, n = 2). Selenuim concentrations were low in all sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 36 publications
0
22
0
2
Order By: Relevance
“…For example, in the agricultural Imperial Valley, Rosenberg and Haley (2004) reported that these 3 orders were the most frequent prey found in pellets. In Oregon and Washington sagebrush/disturbed grasslands (Green et al 1993) and central California grasslands (Gervais et al 2000), Coleoptera and Orthoptera were also prevalent species in pellets, as were spiders (Araneae). As in many other studies of Western Burrowing Owls (Gervais et al 2000, Moulton et al 2005, Hall et al 2009), rodents were a major part of the owls' diets in Santa Clara County, composing over 70% of the biomass consumed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, in the agricultural Imperial Valley, Rosenberg and Haley (2004) reported that these 3 orders were the most frequent prey found in pellets. In Oregon and Washington sagebrush/disturbed grasslands (Green et al 1993) and central California grasslands (Gervais et al 2000), Coleoptera and Orthoptera were also prevalent species in pellets, as were spiders (Araneae). As in many other studies of Western Burrowing Owls (Gervais et al 2000, Moulton et al 2005, Hall et al 2009), rodents were a major part of the owls' diets in Santa Clara County, composing over 70% of the biomass consumed.…”
Section: Resultsmentioning
confidence: 99%
“…In Oregon and Washington sagebrush/disturbed grasslands (Green et al 1993) and central California grasslands (Gervais et al 2000), Coleoptera and Orthoptera were also prevalent species in pellets, as were spiders (Araneae). As in many other studies of Western Burrowing Owls (Gervais et al 2000, Moulton et al 2005, Hall et al 2009), rodents were a major part of the owls' diets in Santa Clara County, composing over 70% of the biomass consumed. Rodents were important year-round (although less so in the winter nonbreeding season) for owls living on both park or nonpark land.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its foods habits have been studied patchily throughout its range (e.g., Gervais et al, 2000;York et al, 2002). Studies in South America have included mainly Southern Brazil (e.g., Silva-Porto and Cerqueira, 1990), Central Chile (e.g., Jaksic and Marti, 1981;Schlatter et al, 1980;Torres-Contreras et al, 1994;Yan˜ez and Jaksic, 1979;Zunino and Jofre´, 1999), and some Argentinean agroecosystems (e.g., Bellocq, 1987;Bellocq and Kravetz, 1994;Coccia, 1984).…”
Section: Introductionmentioning
confidence: 99%